EFFECTIVENESS OF DEEP BREATHING EXERCISE (DBE) ON THE HEART RATE VARIABILITY, BP, ANXIETY & DEPRESSION OF PATIENTS WITH CORONARY ARTERY DISEASE - D'silva, Fatima; H., Vinay; Muninarayanappa, N.V. (Journal of Health and Allied Sciences NU, 2014)
Psychosocial risk factors significantly contribute to the morbidity and mortality of patients with cardiovascular disorders. The present study explored the anxiety and depression status of patients with coronary artery disease and evaluated the effect of deep breathing exercise on these psychosocial variables as well as physiological variables like heart rate variability and blood pressure. A randomized control design was adopted for the study. Out of 65 clients eligible for the study, 45 were selected based on inclusion criteria. Patient were trained in Deep breathing exercise (DBE)for 2-3 days, were instructed to practice the exercise twice a day for 10 min for a period of 2 weeks, further instructed to come for follow up to cardiac OPD after 2 weeks. The study findings revealed that majority of the cardiac patients were anxious 39 (86.66%), 23(57.5%) had mild depression and 3(7.5%) were with severe depression. Fischer's exact test revealed a significant association between depression and occupation (p=0.051), monthly income (p=0.031) and co morbid disease (p=0.006, p<0.05). Karl Pearson's correlation coefficient revealed significant positive correlation between anxiety and depression i.e. (r = 0.414, p <0.01). DBE was found to be effective in reducing anxiety and diastolic BP of clients with CAD. But there was no significant reduction in HR, SBP and depression after the intervention.
Keywords: Coronary artery disease (CAD); Deep breathing exercise (DBE); Heart rate variability; Blood pressure; Anxiety; Depression